Embryonic Heat Conditioning Induces TET-Dependent Cross-Tolerance to Hypothalamic Inflammation Later in Life - Rosenberg, Tali; Kisliouk, Tatiana; Cramer, Tomer; Shinder, Dmitry; Druyan, Shelly; Meiri, Noam (Frontiers in Genetics, 2020)
Early-life encounters with stress can lead to long-lasting beneficial alterations in the response to various stressors, known as cross-tolerance. Embryonic heat conditioning (EHC) of chicks was previously shown to mediate resilience to heat stress later in life. Here we demonstrate that EHC can induce cross-tolerance with the immune system, attenuating hypothalamic inflammation. Inflammation in EHC chicks was manifested, following lipopolysaccharide (LPS) challenge on day 10 posthatch, by reduced febrile response and reduced expression of LITAF and NFκB compared to controls, as well as nuclear localization and activation of NFκB in the hypothalamus. Since the cross-tolerance effect was long-lasting, we assumed that epigenetic mechanisms are involved. We focused on the role of ten-eleven translocation (TET) family enzymes, which are the mediators of active CpG demethylation. Here, TET transcription during early-life stress was found to be necessary for stress resilience later in life. The expression of the TET family enzymes in the midbrain during conditioning increased in parallel to an elevation in concentration of their cofactor α-ketoglutarate. In-ovo inhibition of TET activity during EHC, by the α-ketoglutarate inhibitor bis-2-(5-phenylacetamido-1,3,4-thiadiazol-2-yl) ethyl sulfide (BPTES), resulted in reduced total and locus specific CpG demethylation in 10-day-old chicks and reversed both thermal and inflammatory resilience. In addition, EHC attenuated the elevation in expression of the stress markers HSP70, CRHR1 and CRHR2, during heat challenge on day10 posthatch. This reduction in expression was reversed by BPTES. Similarly, the EHC-dependent reduction of inflammatory gene expression during LPS challenge was eliminated in BPTES-treated chicks. Thus, TET family enzymes and CpG demethylation are essential for the embryonic induction of stress cross-tolerance in the hypothalamus.